A Disneyland Dilemma: Two-Part Tariffs for a Mickey Mouse Monopoly - Oi, Walter Y. (Quarterly Journal of Economics, 1971)
I. Two-part tariffs and a discriminating monopoly, 78.—II. Determination of a uniform two-part tariff, 81.—III. Applications of two-part tariffs, 88.—Appendix: Mathematical derivation of a uniform two-part tariff, 93.